1983
DOI: 10.1042/bj2130131
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the ordering of lipids in the membrane of Dunaliella in response to osmotic-pressure changes. An e.s.r. study

Abstract: Changes in the ordering and motion of lipids in response to changes in the external solute concentration have been studied by using the 5-nitroxide stearate (5NS) and 16-nitroxide stearate (16NS) spin probes in the plasma membrane of the halotolerant unicellular alga Dunaliella salina. Increases in ordering of the 5NS probe and decreases in motion of the 16NS probe were observed in cells equilibrated over 18 h at increasing NaCl concentrations. These changes probably resulted from the influence of the high NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Salt-induced changes in organellar membranes, such as the expression of ER fatty acid elongase, were also reported (7). High salinity also affects sodium transport (8), lipid organization (9,10), and activation of PM protein kinases (11). Taken together, the accumulated evidence suggested that short and long range reorganization of the structure and composition of the PM is at the core of molecular mechanisms responsible for the salinity response.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Salt-induced changes in organellar membranes, such as the expression of ER fatty acid elongase, were also reported (7). High salinity also affects sodium transport (8), lipid organization (9,10), and activation of PM protein kinases (11). Taken together, the accumulated evidence suggested that short and long range reorganization of the structure and composition of the PM is at the core of molecular mechanisms responsible for the salinity response.…”
mentioning
confidence: 82%
“…Early studies in Dunaliella reported global changes in plasma membrane fluidity in response to osmotic shock. Specifically hyperosmotic shocks resulted in rigidification, whereas hypoosmotic shocks led to transient fluidization of the membrane core (9,10,14). Moreover we previously showed that sterols have a crucial role in osmotic sensing in D. salina (61).…”
Section: A Functional Network Involved In Salinity Tolerancementioning
confidence: 99%
“…from Acanthamoeba castellani [30], mouse mastocytoma cells [29], rat macrophages [24], human lens [31], renal brush-border membranes of rabbit [13], and outer membranes of Dunaliella salina [9]. The nature of the spectral changes suggested that these effects were not due to perturbations in membrane structure, but were a consequence of radical interactions resulting from spin probe clustering [7,20].…”
Section: Introductionmentioning
confidence: 99%
“…salina has mainly focused on the glycerol metabolism pathway and also the involvement of the plasma membrane (Curtain et al . ; Zelazny et al . ; Katz et al .…”
Section: Introductionmentioning
confidence: 99%